Cellular Automata and Discrete Complex Systems 19th International Workshop, AUTOMATA 2013, Gießen, Germany, September 14-19, 2013, Proceedings - Kari, Jarkko; Kutrib, Martin; Malcher, Andreas (Theoretical Computer Science and General Issues, 2013)
The volume LNCS 8155 constitutes the refereed proceedings of the 19th International Workshop on Cellular Automata and Discrete Complex Systems, AUTOMATA 2013, held in Giessen, Germany, in September 2013. The 8 papers presented were carefully reviewed and selected from 26 submissions. The scope of the workshop spans the following areas the theoretical and practical aspects of a permanent, international, multidisciplinary forum for the collaboration of researchers in the field of Cellular Automata (CA) and Discrete Complex Systems (DCS), to provide a platform for presenting and discussing new ideas and results, to support the development of theory and applications of CA and DCS (e.g. parallel computing, physics, biology, social sciences, and others) as long as fundamental aspects and their relations are concerned, to identify and study within an inter- and multidisciplinary context, the important fundamental aspects, concepts, notions and problems concerning CA and DCS.